High surface area graphene foams by chemical vapor deposition. (17th October 2016) - Drieschner, Simon; Weber, Michael; Wohlketzetter, Jörg; Vieten, Josua; Makrygiannis, Evangelos; Blaschke, Benno M; Morandi, Vittorio; Colombo, Luigi; Bonaccorso, Francesco; Garrido, Jose A
Abstract: Three-dimensional (3D) graphene-based structures combine the unique physical properties of graphene with the opportunity to get high electrochemically available surface area per unit of geometric surface area. Several preparation techniques have been reported to fabricate 3D graphene-based macroscopic structures for energy storage applications such as supercapacitors. Although reaserch has been focused so far on achieving either high specific capacitance or high volumetric capacitance, much less attention has been dedicated to obtain high specific and high volumetric capacitance simultaneously. Here, we present a facile technique to fabricate graphene foams (GF) of high crystal quality with tunable pore size grown by chemical vapor deposition. We exploited porous sacrificial templates prepared by sintering nickel and copper metal powders. Tuning the particle size of the metal powders and the growth temperature allow fine control of the resulting pore size of the 3D graphene-based structures smaller than 1 μ m. The as-produced 3D graphene structures provide a high volumetric electric double layer capacitance (165 mF cm −3 ). High specific capacitance (100 Fg −1 ) is obtained by lowering the number of layers down to single layer graphene. Furthermore, the small pore size increases the stability of these GFs in contrast to the ones that have been grown so far on commercial metal foams. Electrodes based on the as-prepared GFs can be a boost for the development of supercapacitors, where both low volume and mass are required.